2012
DOI: 10.1016/j.bbabio.2012.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced sensitivity and characterization of photosystem II in transgenic tobacco plants with decreased chloroplast glutathione reductase under chilling stress

Abstract: Chloroplast glutathione reductase (GR) plays an important role in protecting photosynthesis against oxidative stress. We used transgenic tobacco (Nicotiana tabacum) plants with severely decreased GR activities by using a gene encoding tobacco chloroplast GR for the RNAi construct to investigate the possible mechanisms of chloroplast GR in protecting photosynthesis against chilling stress. Transgenic plants were highly sensitive to chilling stress and accumulated high levels of H₂O₂ in chloroplasts. Spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 65 publications
1
24
0
Order By: Relevance
“…Therefore, the complementation of glutathione and ascorbate is essential for maintaining the cellular equilibrium under stress conditions. Similar tendency has also been interpreted in other plant species where involvement of GR becomes a sensible trait for assessing the oxidative stress (Ding et al 2012).…”
Section: Discussionmentioning
confidence: 63%
“…Therefore, the complementation of glutathione and ascorbate is essential for maintaining the cellular equilibrium under stress conditions. Similar tendency has also been interpreted in other plant species where involvement of GR becomes a sensible trait for assessing the oxidative stress (Ding et al 2012).…”
Section: Discussionmentioning
confidence: 63%
“…B–D). Treating plants with specific inhibitors of the chloroplastic translation, such as lincomycin, also can block the PSII repair process, especially D1 protein synthesis in the chloroplast (Mulo et al , Ding et al , Kato et al , Tian et al ). In this study, it was shown that the positive effect of green light on alleviating F v /F m was still observed after treatment with lincomycin under CL (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of GR by RNA interference attenuated GR activity in tobacco and tomato to increase the sensitivity to oxidative and/or chilling stresses (Aono et al 1995;Ding et al 2009Ding et al , 2012Shu et al 2011). In contrast, overexpression of GR in tobacco by chloroplast transformation significantly improved tolerance to methyl viologen (MV), salt and cold stresses (Le Martret et al 2011).…”
Section: Introductionmentioning
confidence: 91%